2020
DOI: 10.1111/ppl.13050
|View full text |Cite
|
Sign up to set email alerts
|

NO and ROS implications in the organization of root system architecture

Abstract: Over the past decades the role of nitric oxide (NO) and reactive oxygen species (ROS) in signaling and cellular responses to stress has witnessed an exponential trend line. Despite advances in the subject, our knowledge of the role of NO and ROS as regulators of stress and plant growth and their implication in signaling pathways is still partial. The crosstalk between NO and ROS during root formation offers new domains to be explored, as it regulates several plant functions. Previous findings indicate that pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 169 publications
(187 reference statements)
0
8
0
Order By: Relevance
“…However, SA also participates in several processes during plant development, such as seed germination, growth, development, stomatal regulation, photosynthesis and fruit ripening (Khan et al 2003; He et al 2010; Pérez‐Llorca et al, 2019). NO signalling is also known to regulate plant growth, development and stress responses in association with other key regulators (Sanz et al, 2015; Asgher et al, 2017; Mukherjee & Corpas, 2020; Prakash et al, 2020). Based on cellular conditions, NO and SA enter into either synergistic or antagonistic relationships in plant development (Rivas‐San Vicente & Plasencia 2011).…”
Section: Crosstalk Between No and Sa In Plant Development Under Stressmentioning
confidence: 99%
“…However, SA also participates in several processes during plant development, such as seed germination, growth, development, stomatal regulation, photosynthesis and fruit ripening (Khan et al 2003; He et al 2010; Pérez‐Llorca et al, 2019). NO signalling is also known to regulate plant growth, development and stress responses in association with other key regulators (Sanz et al, 2015; Asgher et al, 2017; Mukherjee & Corpas, 2020; Prakash et al, 2020). Based on cellular conditions, NO and SA enter into either synergistic or antagonistic relationships in plant development (Rivas‐San Vicente & Plasencia 2011).…”
Section: Crosstalk Between No and Sa In Plant Development Under Stressmentioning
confidence: 99%
“…Review articles herein provide an up‐to‐date coverage of existing progress in this continuously growing research area. Prakash et al () have examined the role of NO and ROS (reactive oxygen species) in governing root system architecture in plants. Rai et al () have given an overview of NO and salicylic acid signaling towards acquired heat tolerance in plants.…”
mentioning
confidence: 99%
“…It is well demonstrated that there is a crosstalk of ROS and NO in many developmental processes [ 63 ], including the establishment of root architecture [ 49 ]. We tested, therefore, whether this crosstalk operates in the At crk5-1 mutant roots.…”
Section: Resultsmentioning
confidence: 99%
“…Of note: the NO depleted roots exhibit elevated levels of reactive oxygen species (ROS) [ 46 ]. The crosstalk between NO and ROS is well demonstrated during various developmental processes including the organization of the root system [ 49 ]. Altogether, the experimental observations indicate that keeping the NO level in an optimal range is required for sustained root growth and development [ 50 ].…”
Section: Introductionmentioning
confidence: 99%